Preparation method of two-dimensional calcium niobate dielectric material and application of two-dimensional calcium niobate dielectric material in miniature transistor

Through chemical vapor deposition method and trace precursor supply method, two-dimensional calcium niobate nanosheets with controllable thickness were prepared, which solved the problem of amorphous state when the thickness of the material is lower than 5nm in the prior art, and achieved high dielectricity Constant and low leakage current characteristics are suitable for the gate insulation layer of microscale field effect transistors.

CN119392364APending Publication Date: 2025-02-07CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411546755.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

It is difficult to prepare ultra-thin oxide dielectric materials with ultra-thin or controllable thickness with high quality, large area, and high dielectric constant, especially in semiconductor devices, when the material thickness is less than 5nm, amorphous state will appear. A good interface cannot be formed.

Method used

Through chemical vapor deposition, the growth kinetics are regulated by using trace precursor supply method and selenium powder-assisted growth method to prepare two-dimensional calcium niobate single crystal nanosheets with controllable thickness. This method has simple process and good repeatability, and can realize the preparation of ultra-thin calcium niobate nanosheets.

Benefits of technology

The preparation of high-quality two-dimensional calcium niobate nanosheets with controllable thickness is realized, the high dielectric constant is maintained, the ultra-small equivalent oxide layer thickness is high, the high breakdown field strength and low leakage current characteristics are suitable for micro-condensation fields. gate insulating layer of effect transistor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392364A_ABST
    Figure CN119392364A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a two-dimensional calcium niobate dielectric material and application of the two-dimensional calcium niobate dielectric material in a miniature transistor. Niobium pentoxide powder and an aluminum oxide plate containing calcium oxide are used as precursors, sodium chloride is used as a fluxing agent, selenium powder is used as a growth promoting factor, mixed gas of argon and hydrogen is used as carrier gas, and a normal-pressure chemical vapor deposition method based on trace precursor supply is adopted. And synthesizing the ultrathin two-dimensional calcium niobate nanosheet at the deposition temperature of 750-900 DEG C. The material has an intrinsic high dielectric constant and an excellent dielectric leakage characteristic, can be applied to a capacitor dielectric layer and a micro field effect transistor back gate dielectric layer, and has an excellent field effect regulation and control capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanomaterials, and specifically relates to a two-dimensional calcium niobate nanosheet dielectric material and a preparation method thereof, and applications in capacitors and field effect transistors. Background Art

[0002] With the rapid development of ultra-large-scale integrated circuits and microelectronic information industries, semiconductor devices are constantly advancing, and the integration of silicon-based chips is constantly increasing and their sizes are constantly shrinking. Integrated circuits are strategic, basic and leading industries that support the development of the national economy and society and safeguard national security. Transistor devices, the core components of integrated circuits, have gone through strained silicon technology, high-κ gate dielectric technology, FinFET technology, and ring-gate transistor technology. Post-Moore era devices need to solve scientific problems such as reduced mobility of short-channel silicon materials, serious instability of heterogeneous interfaces, and significant increase in device power consumption. Two-dimensional materials have the advantages of sub-nanometer atomic layer thickness, no dangling bond surface interface structure, and van der Waals low contact, which can solve the problem of transistor size miniaturization from a physical principle.

[0003] Currently, research on channel materials has been very extensive, mainly focusing on aspects such as the mobility, contact resistance and conductivity type of channel materials, while research on ultra-thin two-dimensional dielectric materials is still in its infancy. The key point of miniaturization of field effect transistors also requires a reduction in the thickness of the silicon oxide insulating layer. When the thickness of the insulating gate oxide is reduced to a few nanometers, the leakage current will be too large, resulting in excessive energy consumption of the device. To address this, the use of high dielectric constant oxides to replace the silicon dioxide insulating layer can achieve a lower equivalent oxide layer thickness. Under the condition of equivalent to 1nm silicon oxide thickness, high κ The oxide layer has a higher physical thickness, which can effectively improve the problem of excessive leakage current and improve device performance. Therefore, it is particularly important to seek two-dimensional high dielectric constant gate materials. In the semiconductor industry, gate materials have been studied in an attempt to replace the commonly used silicon oxide gate layer. As we all know, common high dielectric constant materials, such as h -BN, hafnium dioxide, titanium oxide, aluminum oxide, zirconium oxide, etc. are all three-dimensional structures. At present, these high dielectric constant gate materials can be integrated with silicon-based material devices. The methods for obtaining these two-dimensional metal oxides are mainly through solution method, mechanical stripping, atomic layer deposition, etc. However, with the development of semiconductor devices, the miniaturization of device size has put forward further requirements on the thickness of the material. Due to the limitations of the preparation process, when the material thickness is less than 5nm, an amorphous state will appear, and a good interface between the channel material and the dielectric layer cannot be formed. The preparation of its two-dimensional single crystal film is still a great challenge. Therefore, it is of great significance to develop other ultra-thin single crystal oxide layers with higher dielectric constants and wide band gaps.

[0004] Nowadays, high dielectric constant ( κ >10), wide bandgap ( E g >4eV) are still being discovered, and the latest research has given several new types of high κ Oxides, such as CaF2, α -Sb2O3, SbO 1.93 , β -Bi2SeO5, Sr2Nb3O 10 It is further proved that the high dielectric constant oxide layer plays an important role in achieving the improvement of transistor performance. Therefore, the development of new high-quality, large-area, high-dielectric-constant ultra-thin oxide single crystal dielectric materials remains a long-term and important challenge. Summary of the invention

[0005] The problem to be solved by the present invention is that it is difficult to prepare ultra-thin or controllable thickness ultra-thin oxide dielectric materials of high quality, large area, and high dielectric constant in the prior art. In view of the deficiencies and needs existing in the above background technology, a high dielectric constant two-dimensional calcium niobate single crystal nanosheet is provided. The present invention realizes the preparation of two-dimensional ultra-thin calcium niobate nanosheets by regulating the growth kinetics through chemical vapor deposition. The method has simple process and good repeatability, and the obtained two-dimensional calcium niobate single crystal has high quality, good dielectric properties and controllable thickness.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing two-dimensional calcium niobate nanosheets, which is completed by using atmospheric pressure chemical vapor deposition in a tube furnace, characterized in that the preparation method comprises the following steps: (1) Selecting an aluminum oxide plate containing a trace amount of calcium oxide as a calcium oxide precursor, selecting a certain amount of niobium pentoxide powder as a niobium oxide precursor, selecting a certain amount of ground sodium chloride powder as a flux, and selecting selenium powder as a growth-promoting factor; (2) placing the niobium pentoxide powder and the sodium chloride powder in the alumina plate, placing the alumina plate at the center of the quartz tube of the tube furnace, placing the growth substrate just above the precursor powder, and placing the selenium powder in the front low-temperature zone of the quartz tube; (3) Chemical vapor deposition reaction: using a mixture of rare gas and hydrogen as a carrier gas, the temperature at the center of the tube furnace is raised from room temperature to 750-900°C and kept warm for 10-30 minutes. The temperature of the low-temperature zone at the front end of the quartz tube is set to 300°C. Calcium niobate molecules gradually nucleate and grow on the side of the growth substrate facing the alumina plate. After keeping warm, the growth substrate is naturally cooled to room temperature, and the growth substrate is taken out to obtain the two-dimensional calcium niobate nanosheets.

[0007] As a further preferred technical solution, an aluminum oxide plate containing 0.5wt% calcium oxide is selected as a calcium oxide precursor. The selection of such a trace block solid calcium source can realize the slow and continuous volatilization supply of the calcium oxide precursor, achieve ultra-low kinetic growth, avoid the problem of excessive supply caused by the direct use of calcium oxide or calcium carbonate powder, and is more conducive to the two-dimensional calcium niobate material breaking the three-dimensional isotropic growth mode, thereby achieving in-plane epitaxial growth.

[0008] As a further preferred technical solution, in step (2), the specific operation of arranging the niobium pentoxide powder and the sodium chloride powder in the alumina plate is as follows: spreading the sodium chloride powder on the surface of the alumina plate, and finally spreading the niobium pentoxide powder on the surface of the sodium chloride powder.

[0009] As a further preferred technical solution, the experimental device used for the chemical vapor deposition reaction includes a tube furnace and a gas flow control system, the central constant temperature zone of the tube furnace is about 8 cm, the center position of the quartz tube corresponds to the constant temperature zone in the center of the tube furnace, and the front low temperature zone of the quartz tube corresponds to the low temperature zone of the tube furnace.

[0010] As a further preferred technical solution, the growth substrate may be mica, preferably freshly peeled fluorphlogopite with a size of 10×10 mm and a thickness of 0.04 mm.

[0011] As a further preferred technical solution, in terms of mass ratio, the niobium pentoxide powder: the sodium chloride powder: the selenium powder = (2-20): (1-7): (2-10).

[0012] In the above reaction, niobium pentoxide powder is used as a niobium oxide precursor, and an aluminum oxide plate containing 0.5wt% calcium oxide is used as a calcium oxide precursor. At the same time, ground sodium chloride powder is placed between the two. Under the action of the molten salt-assisted method, calcium oxide and niobium oxide can be volatilized at a lower temperature. This sandwich structure precursor setting method can simultaneously reduce the melting point of calcium oxide and niobium pentoxide powder, and slowly volatilize the above two precursors. The slow and continuous volatilization of the precursor is conducive to the in-plane epitaxial growth of non-layered two-dimensional calcium niobate nanosheets on the substrate. In the above reaction, selenium powder is used as a growth-promoting factor and is placed in the upstream low-temperature zone of the tubular furnace, and the temperature is set to 300°C; As a further preferred technical solution, before the chemical vapor deposition reaction in step (3) begins, a rare gas with a flow rate of 500 sccm is passed for 10 minutes to exhaust the air in the quartz tube; As a further preferred technical solution, the rare gas is any one of helium, neon and argon; preferably, the rare gas is argon.

[0013] As a further preferred technical solution, in the mixed gas of the rare gas and hydrogen, the flow rate Q1 of the rare gas is in the range of 15sccm≤Q1≤300sccm, and can be specifically 15sccm, 20sccm, 25sccm, 30sccm, 35sccm, 40sccm, 45sccm, 50sccm, 55sccm, 60sccm, 65sccm, 70sccm, 75sccm, 80sccm, 85sccm, 90sccm, 95sccm cm, 100sccm, 120sccm, 140sccm, 160sccm, 180sccm, 200sccm, 220sccm, 240sccm, 260sccm, 280sccm, 300sccm, more preferably 20sccm≤Q1≤80sccm; the range of hydrogen flow rate Q2 is ≤7sccm, specifically 0sccm, 1sccm, 2sccm, 3sccm, 4sccm, 5sccm, 6sccm, 7sccm. In this reaction, hydrogen has both the effect of inhibiting nucleation and strong reducibility, so it is very important to adjust the hydrogen flow rate. As the amount of hydrogen introduced increases, the nucleation of the material on the substrate is suppressed, the nucleation has a certain selectivity, niobium oxide and calcium oxide are reacted and nucleated and grown on the substrate, and at this time, the nucleation density on the substrate is low. When the hydrogen flow rate is too high, due to the presence of a lot of hydrogen and hydrogen selenide with strong reducing properties in the quartz tube, niobium oxide is more easily reduced to a low-valent state, thereby growing niobium selenide (NbSe2) on the substrate and failing to obtain calcium niobate.

[0014] As a further preferred technical scheme, the growth time in the above growth process is set to 10-30min; specifically it can be 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min, 25min, 26min, 27min, 28min, 29min, 30min; further preferably is 15-20min. Shortening the growth time can obtain ultrathin calcium niobate nanosheets.

[0015] The second aspect of the present invention provides a two-dimensional calcium niobate nanosheet, which is prepared by the preparation method provided by the first aspect of the present invention. The two-dimensional calcium niobate nanosheet prepared by the preparation method grows in a plane on the surface of a growth substrate, has a morphology of a rectangular thin sheet, a size of 2-40μm, and a thickness of 2-100nm.

[0016] The third aspect of the present invention provides a capacitor, comprising an electrode and a dielectric layer, wherein the dielectric layer is the two-dimensional calcium niobate nanosheet provided by the second aspect of the present invention. The capacitor still maintains a high dielectric constant in the two-dimensional limit, the dielectric constant is 16, and the breakdown field strength of the capacitor is greater than 12 MV·cm -1 .

[0017] As a further preferred technical solution, the electrode comprises a top electrode and a bottom electrode, wherein the material of the electrode is metal, preferably Cr or Au.

[0018] The fourth aspect of the present invention provides a field effect transistor, which includes, from bottom to top, a substrate, a gate electrode, a back gate dielectric layer, a channel layer, and a source and drain electrode deposited on the upper surface of the channel layer, wherein the dielectric layer is the two-dimensional calcium niobate nanosheet provided by the second aspect of the present invention.

[0019] As a further preferred technical solution, the current switching ratio of the field effect transistor is 10 7 , subthreshold swing is 61mV·dec -1 .

[0020] Compared with the prior art, the beneficial technical effects of the present invention are: (1) By using the trace precursor supply method in the atmospheric pressure chemical vapor deposition method, the selenium powder assisted growth method, and the reasonable setting of the precursor laying order and the reasonable adjustment of the hydrogen flow rate, the thickness of the ternary two-dimensional single-crystalline CaNb2O6 nanosheets with controllable thickness can be as low as 2nm. The two-dimensional nanosheet can maintain the high dielectric constant of the bulk material, has an ultra-small equivalent oxide layer thickness, and its 1nm equivalent oxide layer thickness (EOT) can reach 0.26nm, and has high breakdown field strength and low leakage current characteristics.

[0021] (2) By using the two-dimensional calcium niobate nanosheets prepared by the present invention as the dielectric layer, the capacitor still maintains a high dielectric constant in the two-dimensional limit, the dielectric constant is 16, and the breakdown field strength of the capacitor is greater than 12 MV·cm -1 .

[0022] (3) By using the two-dimensional calcium niobate nanosheets prepared by the present invention as the gate dielectric layer of the two-dimensional molybdenum sulfide transistor, an ultra-low subthreshold swing of the transistor (~61mV·dec) is achieved. -1 ), high current switching ratio (~10 7 ), high on-state current (>10 -6 A), significantly improving the performance of miniaturized field-effect transistors. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Figure 2 is a diagram of the experimental apparatus used for material growth in the present invention.

[0024] Figure 2 This is an optical micrograph of the calcium niobate nanosheets prepared in Example 1.

[0025] Figure 3 This is the Raman spectrum of the calcium niobate nanosheets prepared in Example 1.

[0026] Figure 4 This is an atomic force micrograph of the calcium niobate nanosheets prepared in Example 1.

[0027] Figure 5 This is an atomically resolved scanning transmission electron micrograph of the calcium niobate nanosheets prepared in Example 1.

[0028] Figure 6 This is an optical micrograph of the calcium niobate nanosheets prepared in Example 2.

[0029] Figure 7 This is an atomic force micrograph of the calcium niobate nanosheets prepared in Example 2.

[0030] Figure 8 This is an optical micrograph of the calcium niobate nanosheets prepared in Comparative Example 3.

[0031] Fig. 9 This is an atomic force micrograph of the calcium niobate nanosheets prepared in Example 3.

[0032] Fig.10 This is an optical micrograph of the calcium niobate nanosheets prepared in Comparative Example 1.

[0033] Fig.11 Schematic diagram of the structure of the metal / calcium niobate / metal capacitor prepared in Application Example 1.

[0034] Fig.12 This is the dielectric constant test diagram of the capacitor prepared in Application Example 1.

[0035] Fig.13 This is a breakdown field strength test diagram of the capacitor prepared in Application Example 1.

[0036] Fig.14 Schematic diagram of the structure of the molybdenum disulfide transistor prepared in Application Example 2.

[0037] Fig.15 This is the electrical test diagram of the molybdenum disulfide transistor prepared in Application Example 2.

[0038] The figures are marked as follows: 1. growth substrate; 2. quartz tube; 3. alumina plate; 4. top electrode; 5. bottom electrode; 6. dielectric layer; 7. substrate; 8. gate electrode; 9. back gate dielectric layer; 10. channel layer; 11. source and drain electrodes. DETAILED DESCRIPTION

[0039] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0040] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0041] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0042] The present invention is further described in detail below with reference to some specific implementation cases and comparative cases. The present invention adopts chemical vapor deposition method, and the experimental device is as follows: Figure 1 As shown, niobium pentoxide powder and an aluminum oxide plate 3 containing calcium oxide are used as niobium source and calcium source respectively and placed in the central constant temperature zone of a tube furnace 2. Before the tube furnace is heated, a large flow of argon gas is first introduced to exhaust the air in the quartz tube, and then the flow of argon and hydrogen is adjusted to the optimal range, and the tube furnace heating device is started. After the insulation time is completed, the hydrogen is turned off, and the furnace is slowly cooled to room temperature, and high-quality single-crystalline two-dimensional calcium niobate nanosheets are obtained on the growth substrate 1. Example 1

[0043] Weigh 20-200 mg of niobium pentoxide powder and 10-70 mg of sodium chloride respectively, spread the ground sodium chloride powder on the surface of the alumina plate containing calcium oxide, and then spread the niobium pentoxide powder on the sodium chloride, and place it in the constant temperature zone in the center of the tube furnace. Weigh 20-100 mg of selenium powder and place it in a quartz boat, and set it in the upstream low-temperature zone of the tube furnace. Place the freshly peeled fluorphlogopite face down on the precursor, with a size of 10×10 mm, and the distance between the fluorphlogopite growth substrate and the precursor source is about 2-4 mm. Before the tube furnace is heated, first introduce argon gas at a flow rate of 500 sccm for 10 minutes to exhaust the air in the quartz tube, and then keep the argon flow rate Q1=20 sccm and the hydrogen flow rate Q2=6 sccm during the heating and insulation period. The tubular furnace was set to heat up to 800°C at a heating rate of 30°C / min. The temperature of the upstream low-temperature zone of the tubular furnace corresponding to the selenium powder was set to 300°C and kept at this temperature for 20 minutes. After the insulation was completed, the hydrogen gas was turned off to slowly cool the tubular furnace. After the center temperature dropped to room temperature, the argon gas was turned off, and the sample was taken out to obtain an ultra-thin two-dimensional calcium niobate nanosheet on a fluorphlogopite growth substrate. The thickness of the two-dimensional calcium niobate nanosheet was about 4nm. Example 2

[0044] Compared with Example 1, the difference is that the flow rate of hydrogen gas Q2 = 4 sccm.

[0045] Weigh 20-200 mg of niobium pentoxide powder and 10-70 mg of sodium chloride respectively, spread the ground sodium chloride powder on the surface of the alumina plate containing calcium oxide, and then spread the niobium pentoxide powder on the sodium chloride, and place it in the constant temperature zone in the center of the tube furnace. Weigh 20-100 mg of selenium powder and place it in a quartz boat, and set it in the upstream low-temperature zone of the tube furnace. Place the freshly peeled fluorphlogopite face down on the precursor, with a size of 10×10 mm, and the distance between the fluorphlogopite growth substrate and the precursor source is about 2-4 mm. Before the tube furnace is heated, first introduce argon gas at a flow rate of 500 sccm for 10 minutes to exhaust the air in the quartz tube, and then keep the argon flow rate Q1=20 sccm and the hydrogen flow rate Q2=4 sccm during the heating and insulation period. Set the heating program of the tube furnace to heat up to 800℃ at a heating rate of 30℃ / min. At the same time, set the temperature of the upstream low-temperature zone of the tube furnace corresponding to the selenium powder to 300℃ and keep it at this temperature for 20 minutes. After the insulation is completed, turn off the hydrogen gas and let the tube furnace cool down slowly. After the center temperature drops to room temperature, turn off the argon gas and take out the sample. Example 3

[0046] Compared with Example 1, the difference is that the flow rate of hydrogen gas Q2 = 0 sccm.

[0047] Weigh 20-200 mg of niobium pentoxide powder and 10-70 mg of sodium chloride respectively, spread the ground sodium chloride powder on the surface of the alumina plate containing calcium oxide, and then spread the niobium pentoxide powder on the sodium chloride, and place it in the constant temperature zone in the center of the tube furnace. Weigh 20-100 mg of selenium powder and place it in a quartz boat, and set it in the upstream low-temperature zone of the tube furnace. Place the freshly peeled fluorphlogopite face down on the precursor, with a size of 10×10 mm, and the distance between the substrate and the precursor source is about 2-4 mm. Before the tube furnace is heated, first pass argon gas at a flow rate of 500 sccm for 10 minutes to exhaust the air in the quartz tube, and then keep the argon flow rate Q2=20 sccm during the heating and insulation period. Set the tube furnace heating program, heat up to 800℃ at a heating rate of 30℃ / min, and set the temperature of the upstream low-temperature zone of the tube furnace corresponding to the selenium powder to 300℃, and keep it at this temperature for 20 minutes. After the heat preservation is completed, the tube furnace is cooled down slowly. When the center temperature drops to room temperature, the argon gas is turned off and the sample is taken out. Comparative Example 1

[0048] Compared with Example 1, the difference is that no selenium powder is provided in the tube furnace.

[0049] Weigh 20-200 mg of niobium pentoxide powder and 10-70 mg of sodium chloride respectively, spread the ground sodium chloride powder on the surface of the alumina plate containing calcium oxide, and then spread the niobium pentoxide powder on the sodium chloride, and place it in the constant temperature zone in the center of the tube furnace. Place the freshly peeled fluorphlogopite face down on the precursor, with a size of 10×10 mm, and the distance between the fluorphlogopite growth substrate and the precursor source is about 2-4 mm. Before heating the tube furnace, first pass argon gas at a flow rate of 500 sccm for 10 minutes to exhaust the air in the quartz tube, and then keep the argon flow rate Q1=20 sccm and the hydrogen flow rate Q2=6 sccm during heating and insulation. Set the tube furnace heating program, heat up to 800℃ at a heating rate of 30℃ / min, and keep it at this temperature for 20 minutes. After the insulation is completed, turn off the hydrogen and let the tube furnace cool down slowly. After the center temperature drops to room temperature, turn off the argon and take out the sample. Application Example 1

[0050] The sample prepared in Example 1 is used to construct a capacitor with a top electrode / insulating oxide material / bottom electrode structure. First, spin-coat the photoresist on the silicon wafer substrate at a speed of 5000 rpm for 60 seconds, and then pre-bake at 100°C for 60 seconds. After pre-bake, the bottom electrode pattern is exposed using a maskless UV lithography machine, and the exposure time is set to 950ms and the UV light power is 1.5mW. Then, metal Cr / Au (5 / 10nm) is deposited by vacuum thermal evaporation technology. After the deposition is completed, the photoresist is removed using acetone to obtain a bottom electrode 6 of a specific shape. Using a two-dimensional transfer platform, the calcium niobate nanosheet is point-transferred to the bottom electrode 6. Using the same photolithography technology again, the top electrode 4 pattern is exposed on the transferred calcium niobate / bottom electrode surface, and the Cr / Au (10 / 70nm) metal electrode is deposited using a vacuum thermal evaporation device to finally obtain a metal / insulator / metal capacitor sandwich structure. Application Example 2

[0051] The sample prepared in Example 1 was used to construct a transistor device. First, a few-layer graphene was peeled off from a silicon wafer substrate 7 as a transistor gate electrode 8, and a two-dimensional calcium niobate nanosheet was transferred to the graphene electrode as a back gate dielectric layer 9 by combining a transfer platform. A few-layer molybdenum disulfide peeled off mechanically was used as a channel layer 10, and the molybdenum disulfide channel layer 10 was transferred to the surface of the calcium niobate back gate dielectric layer 9. The source and drain electrodes 11 were prepared by electron beam exposure technology combined with vacuum thermal evaporation deposition, and finally a bottom-gate molybdenum sulfide transistor was obtained. The device structure is as shown in FIG. Fig.14 This embodiment shows that the two-dimensional calcium niobate dielectric material prepared by the present invention has high quality, excellent dielectric and leakage properties, and adds another member to the oxide family of gate insulation layer of future miniaturized field effect transistors. Test results analysis

[0052] The optical micrograph of Example 1 of this case is as follows Figure 2 As shown; Raman spectroscopy was performed on the nanosheets obtained in this embodiment, and the Raman spectrum was obtained as shown in Figure 3 As shown, it is at 904cm -1 、538cm -1 、386cm -1 、288cm -1 、240cm -1 、136cm -1 They all have obvious characteristic peaks, which are the same as the Raman vibration peaks of single crystal materials, further demonstrating that the samples are single crystal calcium niobate nanosheets. Figure 4 Shown is an atomic force microscope image of calcium niobate nanosheets grown on the surface of fluorophlogopite in Example 1. The thickness of the sample is 4 nm. Figure 5Shown is a scanning transmission electron microscopy image of calcium niobate nanosheets transferred onto a copper grid. The atomic structure arrangement can be clearly seen, and it is also proved that the growth of the two-dimensional calcium niobate nanosheets makes the exposed surface a (100) crystal plane.

[0053] The optical microscopic image of Example 2 is as follows Figure 6 As shown in the Atomic Force Microscopy image Figure 7 As shown, it can be seen that within a certain range of hydrogen flow rates, in-plane epitaxial growth of two-dimensional calcium niobate nanosheets can be achieved on fluorophlogopite.

[0054] The optical micrograph of Example 3 is as follows Figure 8 As shown, in Example 3, hydrogen is not introduced into the CVD process, and the nucleation density on the growth substrate is relatively high. Two-dimensional calcium niobate nanosheets, nanorods and nanoparticles can be obtained on the fluorphlogopite substrate. The sample shapes are relatively diverse, and the thickness of the calcium niobate nanosheets is relatively thick. It can be seen from Examples 1, 2 and 3 that the method for preparing two-dimensional calcium niobate nanosheets can obtain two-dimensional calcium niobate nanosheets with controllable thickness by controlling the range of hydrogen flow rate Q2 to Q2≤7sccm. The thickness variation is comprehensive. Figure 4 , 7 And 9 can be known.

[0055] The optical micrograph of Comparative Example 1 is as follows Fig.10 As shown, no selenium powder precursor is provided in the CVD process in this comparative example 1. It can be seen that in the absence of selenium powder, the surface of the growth substrate is a disordered nanocluster or a very small nano-short rod-shaped sample, and it is difficult to form a two-dimensional calcium niobate nanosheet product similar to Example 1. By comparing Example 1 with Comparative Example 1, it can be seen that selenium powder has a growth-promoting effect in the synthesis of two-dimensional calcium niobate, and the introduction of a certain amount of selenium powder can effectively promote the in-plane epitaxial growth of two-dimensional calcium niobate nanosheets.

[0056] The side view of the structural diagram of the capacitor of Application Example 1 is as follows Fig.11 The electrical performance of the capacitor obtained in Example 1 was measured using an impedance analyzer E4980A combined with a probe station. By measuring the C- f Changes, further calculations are performed to obtain the changes in dielectric constant with frequency. Fig.12 As shown, it can be seen that calcium niobate can still maintain a high dielectric constant (~16) in the two-dimensional limit. Furthermore, by using the semiconductor analyzer Fs-Pro combined with a probe station to perform electrical measurements on the above device, it was calculated based on the output current-voltage curve that the 10.5nm calcium niobate nanosheet exhibits a dielectric constant of more than 12MV·cm -1 The maximum breakdown field strength is Fig.13 As shown, this indicates that the insulating material has excellent leakage characteristics on a two-dimensional scale, laying the foundation for its potential application value as an oxide insulating layer in miniaturized field-effect transistors.

[0057] The electrical characteristics of the device obtained in Application Example 2 were tested using a semiconductor analyzer B1500 combined with a vacuum probe station. Fig.14 The figure shows the electrical performance of a MoS2 field effect transistor based on two-dimensional calcium niobate. The transistor exhibits the field effect control capability of the contact, such as Fig.15 As shown, its subthreshold swing is as low as 61mV·dec -1 , current switching ratio can reach 10 7 , and at the same time, the leakage current size at the noise level is shown. This application example 2 shows that the two-dimensional high-κ calcium niobate dielectric material prepared by the present invention has high quality, excellent dielectric and leakage properties, and adds another member to the oxide family of gate insulation layers of future miniaturized field effect transistors.

[0058] The above is a detailed introduction to the two-dimensional calcium niobate nanosheets and their preparation methods, capacitors and field effect transistors. The above content is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.

Claims

1. A method for preparing two-dimensional calcium niobate nanosheets, which is accomplished by using atmospheric pressure chemical vapor deposition in a tube furnace, characterized in that: The preparation method comprises the following steps: (1) Selecting an aluminum oxide plate containing a trace amount of calcium oxide as a calcium oxide precursor, selecting a certain amount of niobium pentoxide powder as a niobium oxide precursor, selecting a certain amount of ground sodium chloride powder as a flux, and selecting selenium powder as a growth-promoting factor; (2) placing the niobium pentoxide powder and the sodium chloride powder in the alumina plate, placing the alumina plate at the center of the quartz tube of the tube furnace, placing the growth substrate just above the precursor powder, and placing the selenium powder in the front low-temperature zone of the quartz tube; (3) Chemical vapor deposition reaction: using a mixture of rare gas and hydrogen as a carrier gas, the temperature at the center of the tube furnace is raised from room temperature to 750-900°C and kept warm for 10-30 minutes. The temperature of the low-temperature zone at the front end of the quartz tube is set to 300°C. Calcium niobate molecules gradually nucleate and grow on the side of the growth substrate facing the alumina plate. After keeping warm, the growth substrate is naturally cooled to room temperature, and the growth substrate is taken out to obtain the two-dimensional calcium niobate nanosheets.

2. The method for preparing two-dimensional calcium niobate nanosheets according to claim 1, characterized in that: The content of calcium oxide in the aluminum oxide plate is 0.5wt%; the specific operation of arranging the niobium pentoxide powder and the sodium chloride powder in the aluminum oxide plate in the step (2) is as follows: spreading the sodium chloride powder on the surface of the aluminum oxide plate, and finally spreading the niobium pentoxide powder on the surface of the sodium chloride powder.

3. The method for preparing two-dimensional calcium niobate nanosheets according to claim 2, characterized in that: By mass ratio, the niobium pentoxide powder: the sodium chloride powder: the selenium powder = (2-20): (1-7): (2-10).

4. The method for preparing the two-dimensional calcium niobate nanosheets according to any one of claims 1 to 3, characterized in that: The rare gas is any one of helium, neon and argon.

5. The method for preparing the two-dimensional calcium niobate nanosheets according to any one of claims 1 to 3, characterized in that: In the mixed gas of the rare gas and hydrogen, the range of the rare gas flow rate Q1 is 15 sccm≤Q1≤300 sccm, and the range of the hydrogen flow rate Q2 is Q2≤7 sccm.

6. A two-dimensional calcium niobate nanosheet, characterized in that: The two-dimensional calcium niobate nanosheets are prepared by the preparation method described in any one of claims 1-5.

7. A capacitor comprising an electrode and a dielectric layer, characterized in that: The dielectric layer is the two-dimensional calcium niobate nanosheet according to claim 6; the capacitor still maintains a high dielectric constant in the two-dimensional limit, the dielectric constant is 16, and the breakdown field strength of the capacitor is greater than 12 MV·cm -1 .

8. The capacitor according to claim 7, characterized in that The electrodes include a top electrode and a bottom electrode, wherein the material of the electrodes is metal.

9. The capacitor according to claim 7 or 8, characterized in that: The material of the electrode is Cr or Au.

10. A field effect transistor, comprising, from bottom to top, a substrate, a gate electrode, a back gate dielectric layer, a channel layer, and a source and drain electrode deposited on the upper surface of the channel layer, characterized in that: The dielectric layer is the two-dimensional calcium niobate nanosheet according to claim 6; the current switching ratio of the field effect transistor is 10 7 , subthreshold swing is 61mV·dec -1 .